PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PT. ERAJAYA SWASEMBADA, Tbk (Studi Kasus Toko Erafone ITC Cempaka Mas) - Tini Juartini (Jurnal Ekonomi dan Industri, 2022)
Based on the results of the study, the following conclusions can be drawn there is a significant effect between service quality on customer satisfaction at the Erafone ITC Cempaka Mas store. There is a significant influence between price on customer satisfaction at the Erafone ITC Cempaka Mas store. There is a significant effect between service quality and price simultaneously on customer satisfaction at the Erafone ITC Cempaka Mas toko store.